Changes in the organizational context and the communication between actors following the implementation of intranet (Journal of Information Systems and Technology Management, 2007)
This exploratory and comparative study of two companies examines, based on multiple theoretical models of technology, the diverse relationships that develop between the Intranet and social actors. One of the analyzed companies operates in the software industry, while the other manufactures electronic components. Our research findings are threefold. Firstly, as suggested by the "technological imperative" model, we notice that the Intranet impacts several structural aspects in the organizational contexts under investigation. Secondly, we support the "strategic choice" model, which shows that the Intranet is a social construct that is created, used and changed by the human actors' meaningful actions. Finally, based on the structurationalmodel of Intranet, we observe that several dimensions of communication between the social actors are significantly modified as a result of the dialectical, structurational and continuous interaction that is established between the Intranet and its users. However, although the observed changes take place within the two sample companies, the quantity, the level and intensity of the changes vary according to the organizational context, which is typical of the analyzed company, and the type of industry in which the company operates.